THE INFLUENCE OF E-COMMERCE ON BUYER INTEREST (STUDY ON STUDENTS OF THE ISLAMIC ECONOMICS STUDY PROGRAM AT IAIN AMBON) - Retno, Retno Widia Astuti (PT. Jurnal Center Indonesia Publisher, 2025)
This research is motivated by the condition of online buying and selling competition which is increasingly growing day in the community especially the students of syariah economic study program so that make the buyer interest. Companies or stores should further develop ideas for customer satisfaction to continue to be interested in buying in e-commerce. This research formulates the problem of whether e-commerce has an effect on buyer's interest and how much e-commerce influence to buyer interest of syariah economy study program at IAIN Ambon. In this study, data were collected through questionnaire method to 32 respondents who had made a purchase in e-commerce in IAIN Ambon economic study program using research method is Research Type, Research Type, Research Data Sources, Data Collection Method, Population and sample, Technique Data Processing, Quantitative Data Analysis Technique. The result of this research indicate that there is e-commerce influence to buyer interest proved by t test value show the number 9,649 and its significance 0.000 <0,05 from result above hence there is significant influence between e-commerce and buyer interest. The result of determination coefficient analysis (R2) shows how big influence e-commerce to buyer interest that is 0,748 meaning 7,48% and the rest 25,2% influenced by other variable not discussed in this research.